مساهمة تفسير البغوي في توجيه المعنى الكنائي: دراسة تطبيقية على آيات مختارة من القرآن الكريم: The contribution of al-Baghawī’s exegesis in guiding metonymic meaning: An applied study on selected Quranic verses - Abdullah, Nasimah; Abd Rahman, Lubna; Samsudin, Saifulah; Alaoui, Mohamed Ismaili (al-Irsyad: Journal of Islamic and Contemporary Issues, 2026)
Al-Baghawī was a distinguished Quranic exegete of the 5th century AH. He is renowned for Ma‘ālim al-Tanzīl, which is regarded as one of the significant works of Quranic exegesis that has garnered continuous scholarly attention from the past to the present. Despite the esteemed scholarly status of al-Baghawī’s exegesis and its extensive use by exegetes and researchers, previous studies provide limited substantive discussion of his contributions to the rhetorical aspects of the Quran, particularly metonymy and metonymic meaning. This gap raises important questions regarding the depth of his rhetorical analysis, especially in comparison with exegetes renowned for their expertise in this field, such as al-Rāzī and al-Zamakhsharī. Accordingly, this study aimed to highlight the rhetorical indications presented by al-Baghawī to demonstrate his distinctive contribution to the field of rhetoric. This study employed a descriptive qualitative approach to data collection and analysis, with particular emphasis on textual analysis. The primary focus was on metonymy in its analytical and applied investigation. To fulfil the objective, four textual samples were selected using purposive sampling. The samples were al-Nisā’ verse 21, al-A‘rāf verse 189, and al-Ḥajj verses 8, 9 and 11. The analysis revealed clear contributions of al-Baghawī’s exegesis to rhetorical indications, as he explicitly highlighted significant metonymic constructions. Although al-Baghawī’s exegesis does not extensively focus on the rhetorical analysis of the Quranic verses as some other rhetorical tafsirs, it remains a valuable reference for understanding metonymic meanings, particularly in verses containing metonymy. Therefore, this study recommends al-Baghawī’s exegesis in studies of rhetorical metonymy.